Disclosure of Traditional and Complementary Medicine Use and its Associated Factors to Medical Doctors Among the Longhouse Community in Julau, Sarawak - Noorzilawati, Sahak; Jeffery, Stephen (UNIMAS Publisher, 2022)
Traditional and Complementary Medicine (TCM) practice is increasing worldwide and Malaysia is no exception. Despite the wide use of TCM by the population, there seems to be an issue of not disclosing TCM use to their medical doctor. The aim was to explore the related factors that influence the disclosure of TCM use to medical doctor among respondents in selected longhouses in Sarawak. A cross-sectional study was conducted on 90 respondents from selected Iban longhouses in Julau, Sarikei District. Data were collected using face-to-face interview based on questionnaire consisted of sociodemographic characteristics, TCM use and disclosure, health profile, healthcare utilization and attitude towards TCM. To determine the factors related to disclosure of TCM use, independent t-test and Chi-square (χ2) test was used to examine the relationship between various variables and disclosure of TCM use. The mean age of studied participants was 45.20 (±14.92) years and 80% were married. The prevalence of ever used of TCM treatment was 70%. The rate of disclosure of TCM use among respondents was 27%. Univariate analyses yielded three main factors that significant associated with the disclosure of TCM use among respondents which were education level, presence of chronic diseases and type of chronic diseases (heart disease). The rate of disclosure of TCM use in this study is very low consistent with other local and foreign studies. Thus, other relevant factors that are not studied need to be further explored for better understanding in order to have better integration between TCM and current health system.